The generation and evaluation of recombinant human IgA specific for Plasmodium falciparum merozoite surface protein 1-19 (PfMSP1₁₉) - Shi, J; McIntosh, R; Adame-Gallegos, J; Dehal, P; van Egmond, M; van de Winkel, J; Draper, S; Forbes, E; Corran, P; Holder, A; Woof, J; Pleass, R (BioMed Central, 2011)
Background: Human immunoglobulin G (IgG) plays an important role in mediating protective immune responses to malaria. Although human serum immunoglobulin A (IgA) is the second most abundant class of antibody in the circulation, its contribution, if any, to protective responses against malaria is not clear. Results: To explore the mechanism(s) by which IgA may mediate a protective effect, we generated fully human IgA specific for the C-terminal 19-kDa region of Plasmodium falciparum merozoite surface protein 1 (PfMSP119), a major target of protective immune responses. This novel human IgA bound antigen with an affinity comparable to that seen for an epitope-matched protective human IgG1. Furthermore, the human IgA induced significantly higher NADPH-mediated oxidative bursts and degranulation from human neutrophils than the epitope-matched human IgG1 from which it was derived. Despite showing efficacy in in vitro functional assays, the human IgA failed to protect against parasite challenge in vivo in mice transgenic for the human Fcα receptor (FcαRI/CD89). A minority of the animals treated with IgA, irrespective of FcαRI expression, showed elevated serum TNF-α levels and concomitant mouse anti-human antibody (MAHA) responses. Conclusions: The lack of protection afforded by MSP119-specific IgA against parasite challenge in mice transgenic for human FcαRI suggests that this antibody class does not play a major role in control of infection. However, we cannot exclude the possibility that protective capacity may have been compromised in this model due to rapid clearance and inappropriate bio-distribution of IgA, and differences in FcαRI expression profile between humans and transgenic mice.